2018 Review of Facilities for Low-Income Countries. (Policy Papers; Policy Paper, 2018)
The Fund is facing strong demand for financing from low-income countries (LICs). Commodity price shocks and loose fiscal policies have contributed to rising debt levels and financing needs in many countries. Several developing states, especially smaller ones, are also increasingly vulnerable to large natural disasters. At the same time, many LICs less dependent on commodity exports have enjoyed robust growth in recent years, with more contained vulnerabilities.